Between Toleration and Emancipation: The Self-Empowerment of Jewish Intellectuals in the Habsburg Monarchy - Hecht, Louise (Religions, 2017)
Analyzing a sample of prominent Jewish intellectuals from the Bohemian lands, this article explores Jewish networks as well as cultural and political activism in the Vormärz period and during the 1848 revolution. It seeks to answer the question of whether Joseph II's Edicts of Toleration' had, unintentionally, generated a new group within Jewish society that was determined to fight for their rights. Already during the Vormärz period, these Jewish intellectuals enjoyed a high level of social integration, but also fought the repressive structure of the Metternich regime. After the removal of legal discriminations in 1867, the majority felt a deep sense of loyalty to the state and significantly enriched the cultural and political life of the Monarchy.